2022
DOI: 10.3390/ijms232113446
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Protocols Used in Electrical Pulse Stimulation of Cultured Cells for Mimicking In Vivo Exercise: A Systematic Review, Meta-Analysis, and Meta-Regression

Abstract: While exercise benefits a wide spectrum of diseases and affects most tissues and organs, many aspects of its underlying mechanistic effects remain unsolved. In vitro exercise, mimicking neuronal signals leading to muscle contraction in vitro, can be a valuable tool to address this issue. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines for this systematic review and meta-analysis, we searched EMBASE and PubMed (from database inception to 4 February 2022) for relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…We think this discrepancy may be due to the long intervention time of EPS. Previous research showed that the increase in duration will lead to a significant downward trend in the effect of EPS [ 65 ]. Basically, mechanical stress is an important factor causing muscle hypertrophy in in vitro models, so, it is necessary to explore the conditions that promote muscle hypertrophy solely under EPS in the 3D-EM to mimic hypertrophic effects seen in the 2D muscle cells, such as duration and frequency of EPS, which might be important factors to mediate specific cellular signaling [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…We think this discrepancy may be due to the long intervention time of EPS. Previous research showed that the increase in duration will lead to a significant downward trend in the effect of EPS [ 65 ]. Basically, mechanical stress is an important factor causing muscle hypertrophy in in vitro models, so, it is necessary to explore the conditions that promote muscle hypertrophy solely under EPS in the 3D-EM to mimic hypertrophic effects seen in the 2D muscle cells, such as duration and frequency of EPS, which might be important factors to mediate specific cellular signaling [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This low-frequency EPS technique has been proven to increase glucose uptake, mitochondrial content, cellular oxidation, citrate synthase activity, insulin sensitivity, activation of AMPK, IL-6, and anti-inflammatory activity [146,151,152]. Different EPS protocols exist today, and new ones are continuously being developed to mimic various forms of exercise training, and each has its pros and cons [153]. Although EPS cannot replicate all the conditions of in vivo exercises, as it lacks motor neurons, neuromuscular junctions, blood flow, and innervation, it still has great potential in the study of muscle contraction in myotubes in vitro.…”
Section: Exercise In Managing Cancer Cachexiamentioning
confidence: 99%
“…Studies that used EPS as an in vitro model of exercise mimicking acute versus chronic or aerobic versus resistance training have mostly been described in the immortalized rodent cell lines C2C12 and L6 (24,25). From our review of the literature, 10 studies defined their EPS protocol as that of an "exercise-like" treatment on HSkMCs (26)(27)(28)(29)(30)(31)(32)(33), investigating exercise-mediated signaling mechanisms (26,(28)(29)(30)32,33), expression of mitochondrial-related genes (21,27,31), substrate metabolism (27,28,30,33,56), and measurements of mitochondrial quantity (27,28,(30)(31)(32)(33)) (Table ).…”
Section: Electrical Pulse Stimulationmentioning
confidence: 99%
“…A direct comparison of an in vitro EPS protocol to a specific in vivo mode of exercise has been complicated to recreate. There is no current consensus as to what EPS parameters should be used, (i.e., voltage, time, duration, and frequency of pulses), to mimic any type of exercise training (24). Whether EPS protocols mimic either aerobic or resistance exercise training is still under debate because of the usage of supraphysiological stimulation levels.…”
Section: Electrical Pulse Stimulationmentioning
confidence: 99%